The root of influence: root-associated bacterial communities alter resource allocation in seagrass seedlings - Randell, Anthony S.; Tanner, Jason E.; Wos-Oxley, Melissa L.; Catalano, Sarah R.; Keppel, Gunnar; Oxley, Andrew P. A. (Frontiers in Marine Science, 2023)
Introduction Seagrass roots harbour diverse assemblages of microorganisms that likely benefit the growth and survival of meadows. Yet, restoration efforts rarely consider their effect on developing seagrass seedlings. Sediment origin should determine the types of rhizosphere and root-colonising (rhizoplane) microorganisms and thus the performance of seedlings during restoration, particularly for slow growing climax species like Posidonia. Recent Posidonia restoration attempts in South Australia used commercially sourced 'play pit sand' for seedling propagation and planting, but have been impacted by high mortality. More natural substrates like seagrass meadow sediment have not been previously investigated for suitability over conventional substrates with regard to seedling growth and survival. Methods To assess the relevance of seagrass associated microorganisms in the growth of Posidonia angustifolia seedlings, we investigated the bacterial communities from tank-raised seedlings propagated in autoclave treated and untreated 'play pit sand' and meadow mix (comprising a 1:3 ratio of natural meadow sediment and beach sand) over a 12-week period. Autoclave treatment was adopted in order to diminish the bacterial load prior to planting and thus inform their contribution (if any) on early seedling growth. Samples for bacterial community analysis and seedling growth measurements (numbers and total length of roots/leaves, root diameter, seedling weight, starch reserves) were taken at 4 and 12 weeks. Bacterial assemblages were surveyed from DNA extracts from bulk and rhizosphere sediments and root tissues, as well as from swabs of P. angustifolia fruit, established meadow sediment and water samples prior to seedling propagation, by constructing Illumina 16S rRNA gene libraries. Results While most growth measurements did not vary significantly between sediment type or treatment, proportional growth of roots versus leaves (as expressed as a pseudo root:shoot ratio) was significantly related to treatment, sediment type and seed length. Seedlings from meadow mix invested more in leaves, regardless of treatment, when compared to play sand. Autoclave treatment increased investment in roots for play sand but increased the investment in leaves for meadow mix. Bacterial communities differed significantly between sediments and between sample types (bulk, rhizosphere and roots), with the roots from meadow mix seedlings containing an increased abundance of various potentially beneficial bacterial taxa. Discussion While such changes appear to affect the early development of seedlings, bacterial community dynamics are also likely coupled to changes in nutrient availability. Further research is thus required to disentangle host seedling growth-nutrient-bacterial community dynamics with the view to identifying microbes that may support the growth and vigour of seedlings under different nutrient conditions as part of future restoration efforts.